2017
DOI: 10.1007/978-981-10-4307-9_8
|View full text |Cite
|
Sign up to set email alerts
|

The Non-cardiomyocyte Cells of the Heart. Their Possible Roles in Exercise-Induced Cardiac Regeneration and Remodeling

Abstract: The non-cardiomyocyte cellular microenvironment of the heart includes diverse types of cells of mesenchymal origin. During development, the majority of these cells derive from the epicardium, while a subset derives from the endothelium/endocardium and neural crest derived mesenchyme. This subset includes cardiac fibroblasts and telocytes, the latter of which are a controversial type of "connecting cell" that support resident cardiac progenitors in the postnatal heart. Smooth muscle cells, pericytes, and endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 100 publications
0
21
0
1
Order By: Relevance
“…Suciu et al [2010] studied telopode dynamics using time-lapse video microscopy, although they did not use any markers to achieve a positive distinction. Therefore, cardiac TCs were considered to be "a controversial DOI: 10.1159/000497194 type of connecting cell" [Varga et al, 2017b]. During different studies concerning TCs, care was taken to distinguish them from fibroblasts [Ibba-Manneschi et al, 2016] but not from other cell types, such as endothelial, vascular, and lymphatic cells, or from pericytes.…”
Section: Tc Markersmentioning
confidence: 99%
“…Suciu et al [2010] studied telopode dynamics using time-lapse video microscopy, although they did not use any markers to achieve a positive distinction. Therefore, cardiac TCs were considered to be "a controversial DOI: 10.1159/000497194 type of connecting cell" [Varga et al, 2017b]. During different studies concerning TCs, care was taken to distinguish them from fibroblasts [Ibba-Manneschi et al, 2016] but not from other cell types, such as endothelial, vascular, and lymphatic cells, or from pericytes.…”
Section: Tc Markersmentioning
confidence: 99%
“…The data showed that 55 fetal genes were expressed in LAD-ligated hearts; the downregulated genes included Nbl1, Myoz2, Lbh, Gfra1, Gpx3 and Efemp , while the upregulated genes were Tnc, Anp32b, Thy1, Lpar4 and Car3 132 . ECs participate in controlling CM contraction function as well as wound healing after pathological stress by secreting various biologically active substances, such as adhesion molecules (ICAM-1 and tenascin-C), pro-fibrotic cytokines (endothelin-1, Ang II, TGFβ1, periostin, and connective tissue growth factor), pro-inflammatory mediators (IL-6 and IL-1β), pro-angiogenetic factors (VEGF, PLGF, PDGF, bFGF, EGF, and HGF), cardioprotective mediators (follistatin-like 1, IGF-1, dickkopf-3, apelin, and LIF), some CXC chemokines, and other effectors 133 - 135 .…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…However, recent studies show that moderate exercise is an effective measure to prevent and treat cardiovascular diseases (Achttien et al, 2015). It is clear that exercise can upregulate FSTL1 levels to promote cardiomyocyte proliferation, and the mechanism by which exercise promotes cardiovascular health may be related to exercise‐induced cardiomyocyte proliferation (Bei et al, 2017; Varga, Kyselovic, Galfiova, & Danisovic, 2017). This may be the protective effect of exercise on heart and the mechanism of stress repair (Shen et al, 2017).…”
Section: Mechanism Of Fstl1 Regulating Cardiomyocyte Proliferationmentioning
confidence: 99%